Soil water balance and root development in Rooibos (Aspalathus linearis) plantations under Clanwilliam field conditions - Van Schalkwyk, Roeline (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScAgric)--Stellenbosch University, 2018.